1989
DOI: 10.1111/j.1365-2133.1989.tb01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Nail dystrophy in cutaneous T-cell lymphoma

Abstract: A case is reported of cutaneous T-cell lymphoma in an elderly woman. Dystrophy of all 20 nails was caused by a lymphomatous infiltrate of the nail apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Tomsick [13 ]first described the presence of subungual hyperkeratosis in a patient with multiple MF plaques and circulating Sézary cells. Dalziel et al [10] similarly described marked subungual hyperkeratosis with roughened nail plates and loss of normal sheen in an elderly woman with true erythrodermic SS. A review of 5 SS cases found that all 5 patients presented with splinter hemorrhages in at least 5 nails.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomsick [13 ]first described the presence of subungual hyperkeratosis in a patient with multiple MF plaques and circulating Sézary cells. Dalziel et al [10] similarly described marked subungual hyperkeratosis with roughened nail plates and loss of normal sheen in an elderly woman with true erythrodermic SS. A review of 5 SS cases found that all 5 patients presented with splinter hemorrhages in at least 5 nails.…”
Section: Discussionmentioning
confidence: 99%
“…Nail involvement is a common clinical feature of SS that may include yellow discoloration, nail plate thickening [10,11,12], subungual hyperkeratosis [10,13,14,15], onychodystrophy [15], splinter hemorrhages [14], onychomadesis [12,15], trachyonychia [15], and/or indentations of the nail [14]. Tomsick [13 ]first described the presence of subungual hyperkeratosis in a patient with multiple MF plaques and circulating Sézary cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nail fragility was another finding in our study, which was manifested with nail plate destruction and fragility. In the literature, we have found one case report by Dalziel et al [9] of 20-nail dystrophy in a patient with progressive cutaneous T-cell lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentations of nail involvement in previous case reports included subungual hyperkeratosis, onycholysis, onychomadesis, yellow discoloration, thinning of the nail plate, splinter hemorrhage, and 20-nail dystrophy [2,3,4,5,6,7,8,9,10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation